MODELLING OF ROUGH RICE SOLAR DRYING UNDER NATURAL CONVECTION - Ahou, Konan; Emmanuel, Assidjo Nogbou; Patrice, Kouame; Benjamin, Yao (European Scientific Journal, ESJ, 2014)
In this study, the sun drying behaviour of aromatic rough rice was investigated. Drying experiments were conducted at three different seasons in Ivory Coast. The drying data were fitted to ten different mathematical models. Among the models, the Two-term model was found to best explain thin layer open sun drying behaviour of the rice. The performance of these models was investigated by comparing the determination of coefficient (R²), sum square error (SSE) and root mean square error (RMSE) between the observed and predicted moisture ratios. The effective diffusivity coefficient of moisture transfer during drying, computed on the basis of Fick’s law, was within the range of 8.345.10-12 and 4.517.10-11m2.s-1. In addition, the activation energy was estimated to 68.255 Kj.mol-1.